2020
DOI: 10.9734/air/2020/v21i730216
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assurance in Stereotactic Radiosurgery and Stereotactic Body Radiotherapy

Abstract: Stereotactic radiosurgery (SRS) and stereotactic body radiotherapy (SBRT) have settled down in the center of modern palliative and recently curative intent treatments in the last two decades. Being special, technology-driven, direct knowledge and experience based clinical procedures, both SRS and SBRT require high precision, accuracy and reproducibility to be safely and effectively delivered, which delineates the importance of quality assurance (QA) procedures from head to toe. In this review, we focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…There were only small variations but as SIMT SRS requires very complex treatment plans, 25,29 even slight errors can have negative clinical impacts. 30 The findings relating to jaw tracking of this research are supported by Wu et al 15 that compared identical plans with and without jaw tracking. Though all plans were deemed deliverable, it was found that the passing rate for plans with jaw tracking (96.9%) was slightly lower than with fixed jaws (99.2%) using gamma analysis criteria of 3%/3 mm.…”
Section: Quality Assurancesupporting
confidence: 68%
“…There were only small variations but as SIMT SRS requires very complex treatment plans, 25,29 even slight errors can have negative clinical impacts. 30 The findings relating to jaw tracking of this research are supported by Wu et al 15 that compared identical plans with and without jaw tracking. Though all plans were deemed deliverable, it was found that the passing rate for plans with jaw tracking (96.9%) was slightly lower than with fixed jaws (99.2%) using gamma analysis criteria of 3%/3 mm.…”
Section: Quality Assurancesupporting
confidence: 68%
“…In VMAT SBRT, gantry angles, dose rate, and the MLC positions vary during the radiation delivery, where the QA procedures needed to be able to detect all planning-and machine-related errors for the safe conveyance of the SBRT procedure. 28,48 Liang et al analyzed three VMAT QA systems regarding their sensitivity to machine errors, including the gantry angles, MLC positions, and LINAC outputs. The authors proclaimed that neither of them was satisfactorily sensitive to the simulated output errors with their pros and cons related to sensitivity in different parameters.…”
Section: Discussionmentioning
confidence: 99%
“…As per our institutional guidelines, all QA procedures including patient-specific QA, a daily QA check on kilovoltage to megavoltage, and imaging isocenter coincidences were completed before the delivery of the SBRT. 28 For each plan having VMAT and WO-DCA, a corresponding patient-specific QA plan was also created for measurement in OmniPro I'mRT software version 1.4.3.3 (Scanditronix Wellhofer AB Sweden) with Kodak EDR-2 Ready pack film (Eastman Kodak Company, Rochester, NY) on VIDAR's Dosimetry PRO ® Advantage film scanner (VIDAR Systems Corporation, Herndon, VA). The film scanner was calibrated by using scaled radiation dose and film optical density.…”
Section: Patient-specific Quality Assurance (Qa) and Treatment Deliverymentioning
confidence: 99%
See 1 more Smart Citation